Learning at Your Fingertips: Embracing the Era of Digital Education - Faizal Ansyori; Anggia Faradina (EduTech Journal, 2025)
This study explores the relationship between students’ utilization of digital learning platforms and their readiness for digital-based learning in the context of the post-pandemic education system. As educational institutions shift toward hybrid and fully online models, understanding the behavioral and technological preparedness of students has become a critical concern. Using a quantitative approach, data were collected through surveys distributed to students who actively engaged in digital learning environments. The results show a statistically significant and positive correlation between the frequency and quality of digital platform use and students' readiness, particularly in areas such as self-motivation, time management, digital confidence, and adaptability. However, the study also reveals disparities in digital access and varying levels of behavioral discipline, which affect overall learning outcomes. The findings suggest that digital readiness is a multifaceted construct requiring not only access to technology but also the development of self-regulated learning behaviors. Educators and policymakers must therefore address both technological infrastructure and individual learner competencies to ensure effective digital transformation in education. This research contributes to ongoing discussions about equity, engagement, and the future of education in the digital age.